Sustainable building systems and construction for designers - Tucker, Lisa M.; Samulski, Emily; Miranda, Joseph (New York : Fairchild Books, 2022)
'Author Lisa M. Tucker covers topics in a holistic approach, from the structural (site consideration and foundations) to the experiential (indoor air, acoustics, and safety), making a clear case for interior design professionals to understand their moral responsibilities to people and the environment, and to follow sustainable building practices. Now in its third edition, the award-winning Sustainable Building Systems and Construction for Designers has been updated to reflect current CIDA accreditation standards and include recent industry trends related to interior construction, such as security and well-being. Additionally, a complete set of new case studies has been commissioned. Line drawings, color photography, and sample student work join together to support student learning on this essential and timely topic'--
Includes index.
Keywords: Sustainable construction -- Pictorial works; Sustainable design -- Pictorial works